ПРОГНОЗУВАННЯ ЦІН НА СИРОВИНУ У СІЛЬСЬКОМУ ГОСПОДАРСТВІ - Burbelo, O.A.; Burbelo, S.О. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2016)
In the article possibilities of application of ekonomic-mathematical models are investigational in a management economic security of enterprises. Measures are offered on avoidance of possible risks in their activity. REFERENCES1 Amitan V.N. (2009), Economic security : the concept and the basic model, Ekonomichna kibernetyka, vol. 3-4, pp. 13-202. Bocharnikov V.P., Releckij S.M. and Zaharov K. V. et al. (1997), Riski vo vneshne-jekonomicheskoj dejatel’nosti predprijatij [Risks are in outwardly-economic activity of enterprises], INJEKS, Kyiv, Ukraine3. Vitlins’kyj V.V. (1996), Analiz, otsinka i modeliuvannia ekonomichnoho ryzyku [Analysis, valuation and design of economic risk], Demiur, Kyiv, Ukraine4. Yerina A.M. (2001), Statystychne modeliuvannia ta prohnozuvannia [Statistical design and prognostication], KNEU, Kyiv, Ukraine5. Kozachenko A.V. Ponomarev, V.P. and Ljashenko A.N. (2003), Jekonomicheskaja bezopasnost’ predprijatija: sushhnost’ i mehanizm obespechenija [Economic safety of the enterprise: the nature and mechanism to ensure], Libra, Kyiv, Ukraine6. Kozachenko A.V. and Ponomarev V.P. (2003), Methodical bases of estimation of economic strength of enterprise security, Regional’nye perspektivy, vol. 2-3 (9-10), pp. 104-1067. Korobchyns’kyj O.L. (2009), Method of forming of the system of economic security of enterprise, Aktual’ni problemy ekonomiky, vol. 4, pp. 41-458. Ljannoj G. (2006), Company economic security system, BOS — zhurnal o lichnoj i kommercheskoj bezopasnosti, vol. 7, pp. 16-199. Mel’nyk T.M. (2000), Quantitative analysis of risk valuation, Finansy Ukrainy, vol. 9, pp. 63-6710. Piskunova O.V. (2007), Analysis and valuation of financial risks of activity of small enterprises, Finansy Ukrainy, vol. 8, pp. 119-129.11. Voronkova A.Je., Kozachenko A.V., Ramazanov S.K. and Hlapenov L.E. (2007), Sovremennye tehnologii upravlenija promyshlennym predprijatiem [Modern technologies of management an industrial enterprise], Libra, Kyiv, Ukraine.12. Trydid O.M., Tyzhnenko O.H., and Tyzhnenko L.O. (2009), Ekonomiko-matematychni modeli otsinky finansovoho stanu sub’iektiv hospodariuvannia [Ekonomik-mathematical models of valuation of the financial state of subjects of managements], UBS NBU, Kyiv, Ukraine.13. Yastrems’kyj O.I. (1992), Modeliuvannia ekonomichnoho ryzyku [Design of economic risk], Lybid’, Kyiv, Ukraine.14. Barber S. and Jennison C. (1999) Symmetric tests and confidence intervals for survival probabilities and quantiles of censored survival data, Biometrics, vol. 55, pp. 430–436. https://doi.org/10.1111/j.0006-341X.1999.00430.x15. Alesinskaja T.V. (2009), Osnovy logistiki. Funkcional’nye oblasti logisticheskogo upravlenija [Bases of logistic. Functional areas of logistic management], Izd-vo TTI JUFU, Taganrog, Russia.